A comparative study of learning outcomes between video-based and traditional lecture-based teaching in physiology (Bangladesh Journal of Medical Science, 2021)
Background: -Video-based teaching, a distance learning tools is widely beingused in the present COVID-19 pandemic. Present study compares cognitive and affective domains learning outcomes between traditional and video-based physiology lecture.Methods and material: -A total of 25female students of Applied Medical College, Prince Sattam bin Abdul Aziz University, kingdom of Saudi Arabia during 2019 were selected for the study. Physiology course consist of 45 credit hours in a fifteen-week semester. Students were evaluated by various methods for different levels of cognitive and affective domains between traditional method of endocrine physiology lecture session and video-based digestive physiology lecture session. Marks obtained by each student in all the assessment methods of cognitive and affective domains were calculated to get a total mean score and expressed in percentage and compared between the traditional and video-based physiology lecture.Results: -The total mean score for all the assessment methods of the cognitive domains in the digestive physiology lecture with video was 70% and endocrine lecture without video was 50%.The total mean score for affective domain in the digestive physiology lecture with video was 80% and endocrine lecture without video was 50%.Cognitive domain show no major difference between traditional endocrine physiology and video-based digestive physiology lecture, while student performance was good for affective domain in the lecture supported by video.Conclusion: -Video-based teaching helps the learner to achieve objectives of the different levels of affective domain compared to cognitive domain as well as compared to traditional lecture with no video.Bangladesh Journal of Medical Science Vol.20(4) 2021 p.833-839